PEMBUATAN ARANG AKTIF DARI BATANG JAGUNG MENGGUNAKAN AKTIVATOR ASAM SULFAT DAN PENGGUNAANNYA PADA PENJERAPAN ION TEMBAGA (II) - Suhendra, Dedy; Gunawan, Erin Ryantin (UI Scholars Hub, 2010)
Preparation of Activated Carbon from Maize Stems by Sulfuric Acids Activation and Their Application in Copper (II) Ion Sorption. Activated carbons were prepared from maize (Zea mays L.) stems by sulfuric acids activation or chemical methods. The dry maize stems are usually used as low-value energy resources in many countries, burned in the field, or discarded, which are unfavorable to environment. This motivates the investigation of producing value-added products from the dry maize stems, such as activated carbons, as well as solving some environmental problems. The preparation process consisted of sulfuric acid impregnation at different impregnation ratio followed by carbonization at 250–400 o C for 1–4 h. The results show that the impregnation ratio was 1.25, the optimum activation temperature was 300 o C and the activation time was 1 h. The sorption capacity of the activated carbon was 25.1 mg/g.